1997
DOI: 10.1111/j.1600-0447.1997.tb09932.x
|View full text |Cite
|
Sign up to set email alerts
|

Life events in childhood, adolescence and adulthood and the relationship to panic disorder

Abstract: The aim of this study was to explore the association between stressful life events (SLE) and the development of panic disorder (PD) in an Israeli sample. A total of 44 PD patients and a matched control group were studied with regard to SLE over the life cycle (in childhood, adolescence, adulthood and the year preceding the outbreak of the disorder). The major findings were as follows. (i) With regard to the total number of life events experienced in childhood and adolescence, the PD group had experienced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
2
38
0
1
Order By: Relevance
“…These findings can be interpreted in the light of a theory by Gunnar and Vazquez (11), who hypothesized that stressful influence early in life may provoke frequent elevations in cortisol levels, which would eventually lead to down-regulation of components of the HPA-axis. On the basis of this theory, and the assumption that stress in early life is also associated with a risk for anxiety problems (12,13), one could expect anxiety problems to be associated with relatively low cortisol levels. Taken together, there is still little consensus about whether relatively high or low cortisol levels underlie anxiety problems.…”
Section: Introductionmentioning
confidence: 99%
“…These findings can be interpreted in the light of a theory by Gunnar and Vazquez (11), who hypothesized that stressful influence early in life may provoke frequent elevations in cortisol levels, which would eventually lead to down-regulation of components of the HPA-axis. On the basis of this theory, and the assumption that stress in early life is also associated with a risk for anxiety problems (12,13), one could expect anxiety problems to be associated with relatively low cortisol levels. Taken together, there is still little consensus about whether relatively high or low cortisol levels underlie anxiety problems.…”
Section: Introductionmentioning
confidence: 99%
“…4 Both heritable factors and stressful life events, particularly in early childhood, appear to be associated with the onset of panic disorder. 5 Under normal conditions, the central nucleus of the amygdala serves as a relay for sensory information between the higher cortical centers and the brain stem nuclei. In patients with panic disorder and other anxiety disorders, the central nucleus of the amygdala also receives additional information from the higher cortical centers, which represent cortical processing of the initial sensory information.…”
Section: Neurobiology Of Panic Disordermentioning
confidence: 99%
“…5,6 Currently advised comprehensive treatment strategies are based on the use of medication, CBT, psychosocial therapies, and patient education. Medication has a central role through controlling the biological basis of the panic disorder, i.e., elimination of panic attacks through stabilization of GABAergic and serotonergic neurotransmitter systems, thereby reducing the magnitude of phobic avoidance to a level that can be treated by CBT.…”
Section: The Role Of High-potency Benzodiazepines In the Treatment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…That being said, individual specific environmental conditioning, such as early parental separation or childhood trauma, may also contribute to varying liability to PD. 8,[14][15][16][17] It has also been suggested that neurobiological abnormalities in regions such as the medial prefrontal cortex, brainstem and limbic system (including the temporal lobe, amygdala and hippocampus) mediate PD. 14,[18][19][20] This is in line with the current understanding of the neurocircuitry of fear, in which the amygdala facilitates the processing of sensory input from the cortex to efferent target organs.…”
Section: Pathogenesis Of Panic Disordermentioning
confidence: 99%